2020
DOI: 10.1016/j.annonc.2020.08.796
|View full text |Cite
|
Sign up to set email alerts
|

724P A prospective phase II study of gemcitabine plus platinum in combination with bevacizumab for metastatic renal medullary and collecting duct carcinoma (GETUG-AFU 24, BEVABEL trial)

Abstract: Background: The presence of tumor infiltrating lymphocytes (TILs) is considered a poor prognostic marker in renal cell carcinoma (RCC), unlike in other tumors. We previously investigated prognostic impact of PD-L1 status in RCC after the start of systemic therapy, and found that the prognostic impact of PD-L1 status showed different trends in subgroup of immune phenotype (classification based on spatial localization of CD8 + T cells:Methods: We analyzed 770 patients for both PD-L1 expression (expression in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, unlike most other types of non-clear cell histologies, collecting duct RCCs may respond to cytotoxic chemotherapy using platinum-based chemotherapy as reported in several case reports and trials [62][63][64][65][66]. A specific study, the BEVABEL trial, combining chemotherapy and anti-angiogenics (bevacizumab) was conducted, however this study produced negative results, validating platinumbased chemotherapy as the standard of care [67].…”
Section: Clinical Datamentioning
confidence: 83%
“…Moreover, unlike most other types of non-clear cell histologies, collecting duct RCCs may respond to cytotoxic chemotherapy using platinum-based chemotherapy as reported in several case reports and trials [62][63][64][65][66]. A specific study, the BEVABEL trial, combining chemotherapy and anti-angiogenics (bevacizumab) was conducted, however this study produced negative results, validating platinumbased chemotherapy as the standard of care [67].…”
Section: Clinical Datamentioning
confidence: 83%
“…Another study reported that the triple combination of bevacizumab, gemcitabine, and platinum salt, prolonged progression-free survival (median: 15.1 months) and OS (median: 27.8 months) in five cases of mCDC ( 17 ). However, in a prospective phase II trial of metastatic renal medullary and mCDC, this triple combination strategy was associated with low response rates and severe toxicity ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A report of five patients with metastatic cdRCC treated with triple combination of bevacizumab, gemcitabine and platinum salt followed by maintenance therapy with bevacizumab showing an objective response rate of 60% ( 40 ). Based on these data, a phase II trial was conducted to evaluate the efficacy and safety of this combination in patients with metastatic medullary RCC and cdRCC ( 41 ). From 34 patients enrolled 26 were metastatic cdRCC.…”
Section: Treatmentmentioning
confidence: 99%